PEMBELAJARAN PASSING BAWAH BOLA VOLI MINI MENGGUNAKAN PERMAINAN BOLA GANTUNG (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study is to determine the improvement of learning outcomes passing down using a minivolleyball game ball hanging on Elementary School fourth grade students Srengseng 03 districts pagerbarangtegal district. This study conducted in 4 phases, including planning, action, observation, and reflection usingaction research methods class. Each stage of the meeting shows the learning process of physical education withmaterials volleyball. The subjects were elementary school fourth grade students Srengseng Pagerbarang TegalDistrict 03 in 2013 numbered 20 students. The results based on analysis of the percentage of cycle 1 with apercentage of 55% and 85% cycle 2 increased by 30% with the percentage of successful assessment of indicatorsof success that is expected at 85%. Conclusion of this study indicate that the hanging ball games can improvelearning passing under mini volleyball in grade IV elementary School District 03 Srengseng PagerbarangTegal regency.